Advanced strategies to thwart foreign body response to implantable devices. Issue 3 (2nd March 2022) - Capuani, Simone; Malgir, Gulsah; Chua, Corrine Ying Xuan; Grattoni, Alessandro
Abstract: Mitigating the foreign body response (FBR) to implantable medical devices (IMDs) is critical for successful long‐term clinical deployment. The FBR is an inevitable immunological reaction to IMDs, resulting in inflammation and subsequent fibrotic encapsulation. Excessive fibrosis may impair IMDs function, eventually necessitating retrieval or replacement for continued therapy. Therefore, understanding the implant design parameters and their degree of influence on FBR is pivotal to effective and long lasting IMDs. This review gives an overview of FBR as well as anti‐FBR strategies. Furthermore, we highlight recent advances in biomimetic approaches to resist FBR, focusing on their characteristics and potential biomedical applications.